Analysing Factors Affecting the Nabire Regent’s Accountability Report (LKPJ) Nabire Regency - Suripatty, Petrus Izaach (Advances in Social Sciences Research Journal, 2021)
This study applied qualitative approach through the process of finding, understanding, explaining and obtaining an overview of social phenomena and public phenomena regarding the Synergy of Relations between the Legislative and Executive arms of regency government carrying out the authority of the Accountability Statement Report (LKPJ) of the Regent of Nabire Regency. Data collection techniques applied were; observation, interviews and questionnaires. The data analysis technique applied were qualitative data analysis technique to describe the facts obtained from the results of field studies and literature reviews to clarify the picture of the research results. The results of interviews related to the theory of institutional relations, found a negative and conflicting relationship existing between the two; legislative and executive parties, a position that build a political bargain that benefits each party so that it gives birth to political commitments and deals in the Regent’s LKPJ agreement caused by the sectoral ego of each party. The executives consider themselves as having more understanding than the legislature and vice versa. Another problem is the lack of experience, education and the emergence of election winners as leaders/Chairmen of the Regional People’s Representative Council which is a political party under the leadership of the executive/regent who has an emotional relationship in the form of family relations with the Regent. Suggestions from researchers from the executive side to carry out the Annual LKPJ to the Legislature on time and the need to strengthen the DPRD’s supervisory function on the performance of local governments in order to create good governance. The Nabire DPRD critically and carefully supervises the LKPJ of the Regent of Nabire Regency based on the vision, mission, RPJM and RPPD in a transparent, responsive, efficient, effective, accountable, participatory, measurable, fair and sustainable manner. Publicization of the Regent’s LKPJ document and strengthening of the legislative function through training, comparative studies, as well as the availability of funding to finance experts who can assist with legislative tasks is required.